2016
DOI: 10.1186/s12884-016-0879-y
|View full text |Cite
|
Sign up to set email alerts
|

Better than nothing? maternal, newborn, and child health services and perinatal mortality, Lubumbashi, democratic republic of the Congo: a cohort study

Abstract: Background: The Democratic Republic of Congo (DRC) has a high rate of perinatal mortality (PMR), and health measures that could reduce this high rate of mortality are not accessible to all women. Where they are in place, their quality is not optimal. This study was initiated to assess the relationship between these suboptimal maternal, newborn and child health (MNCH) services and perinatal mortality (PM) in Lubumbashi, DRC's second-largest city. Methods: We conducted a prospective cohort study, comparing women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 58 publications
0
32
0
1
Order By: Relevance
“…Previous research has also highlighted the importance of these variables in ANC attendance. 1,8,19,20 Thus, these variables can be considered confounders in the causal pathway between ANC attendance and PM. Maternal morbidity increases the risk of PM and affects GA; however there is no direct effect of maternal morbidity on ANC attendance, or vice-versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has also highlighted the importance of these variables in ANC attendance. 1,8,19,20 Thus, these variables can be considered confounders in the causal pathway between ANC attendance and PM. Maternal morbidity increases the risk of PM and affects GA; however there is no direct effect of maternal morbidity on ANC attendance, or vice-versa.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of antenatal care (ANC) and subsequent ANC attendance by pregnant women have an influence on pregnancy outcomes. ANC improves maternal and newborn survival because it reduces the risk of preterm birth and perinatal mortality (PM) [1][2][3][4] through individual risk assessment and monitoring. In both highand low-income countries, associations between lack of ANC attendance and adverse pregnancy outcomes have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…2.2 Yobe health situation: like in most states in Nigeria, Yobe operates a pluralistic health care delivery system with orthodox and traditional systems served by 528 health facilities (508 public and 20 private) fairly distributed across the state (YBSG, 2010). As reported in the proceeding of Yobe economic summit, the major health problems afflicting the population of Yobe state were malaria, diarrhoea, respiratory tract infections such as tuberculosis and anaemia, malnutrition, hypertension and HIV/AIDS (Ngama et al, 2009). This poor health situation was further aggravated by the high number of infant, Under 5 and maternal mortality rates mostly associated with poor health service delivery (YBSG, 2010).…”
Section: Methodsmentioning
confidence: 97%
“…These key health challenges were aggravated by an inadequate supply of essential drugs and medical supplies, decaying infrastructure, an inadequate and inequitable mix of professional health workers leading to low morale, weak referral systems and poor coverage across the state (YBSG, 2010). In order to reverse this scenario, the state government organised its first ever State Economic Summit in 2008 which revealed that underlying this negative situation was the general lack of or poor management and weak institutional arrangement that led to the duplication of public health functions, service delivery, poor coordination and inadequate funding (Ngama et al, 2009). With these key public health concerns, Yobe state over the years is therefore not considered to be on the right track in achieving MDGs 4, 5, and 6 which continue to undermine its health development that must be addressed through policy matters.…”
Section: Methodsmentioning
confidence: 99%
“…29 In terms of the distribution of deaths, according to Chapter 15 of the ICD-10, disorders associated with oedema, proteinuria and hypertensive disorders during pregnancy, childbirth and the puerperium (ICD O10-O16) stood out when compared to others, equivalent to an absolute number of 270 (30.5%) cases, similar to the results of other studies. [31][32][33][34] Hypertensive diseases are predominantly found in this group. Childbirth complications, whose absolute number was 194 (ICD O60 -O75) and complications in the puerperium (n = 149) (ICD O85-O92) also had a significantly high value.…”
Section: Discussionmentioning
confidence: 99%